STRUCTURAL AND FUNCTIONAL REACTIONS OF LYMPH NODES TO VARIOUS ANTIGENIC EFFECTS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to a review of the literature on intercellular relationships occurring in the lymph nodes during the immune response. Peculiarities of intercellular relationships during the immune response in response to exposure to an antigen.